A riqueza do élenchos: um estudo sobre a aplicação platônica da prática investigativa socrática - Quinalia Filho, Rineu (2019)
Proposing a presentation regarding élenchos is not an easy task. Élenchos is primarily a synonym of inspection. Everything starts with a simple question: “what is?” (ti estí;). Ti estí basically establishes the relationship between the subject who applies the question (Socrates) and the other who must defend it (almost always a renowned interlocutor). At the start, élenchos has a personal character, a play of roles between someone who asks and another person who answers with fixed guidelines. Two dialogues from Plato’s youth are explored in this thesis: Laches and Charmides. Considering that these dialogues are watched by a supposed audience, we point to an interpretation where the main interlocutors of Socrates could represent a kind of stage, a means to an end, and not the final recipient of the dynamics proposed by the Socratic inspection. The thesis will establish a metaelenctic approach pointing to the interpretation that the Socratic élenchos could be seen under the light of a two-fold orientation: the first one, which is called ‘straight’, would have a dual nature, proposing the inspection of a (famous) other; the second is the ‘oblique’, with a plural nature, aiming at the instruction of (humble) others.